Download presentation
Presentation is loading. Please wait.
Published byKerry Phillips Modified over 9 years ago
1
DIFFERENTIATION Laura Berglind Avery Gibson
2
Definition of Derivative: Lim f(x+h) – f(x) h 0 h Derivative= slope Lim= limit h 0 = as h approaches zero
3
Notations for Derivative f’(x)F prime DyDerivative of y in dxrespect to x y’ y prime
4
Let’s Put the Definition to Practice Example: f(x)=x ² We know the answer is: f’(x)= 2x Lim f(x+h) – f(x)=lim x ²+2xh=h²-x²=lim h(2x+h) h 0 hh 0 hh 0 h When bottom H goes away, you can plug in 0 for h Lim(2x+0) = 2x h 0
5
Thus, you can follow these three simple steps! 1. Replace x with x+h and copy problem 2. Factor and get rid of h 3. Replace h with 0
6
Let’s try one more! Lim f(x+h) – f(x)=lim (x +h)^1/2-x^1/2 h 0 hh 0 h f(x)= √x Think of this problem as: f(x)= x^1/2 lim (x +h)^1/2-x^1/2 * (x +h)^1/2+x^1/2 h 0 h *multiple by the conjugate (x +h)^1/2=x^1/2 lim x +h-x______= lim ___1_______ h 0 h [(x+h)^1/2 + x^1/2]h 0 (x+h)^1/2 + x^1/2 = 1______= 1____=1/2x^-1/2 (x+0)^1/2 +x^1/2 2x^1/2
7
Old Rules to remember! Lim sinh = 1 h 0 h Lim 1-cosh = 0 h 0 h *Sin(x+h) = sinxcosh + cosxsinh *Cos(x+h) = cosxcosh - sinxsinh Before we move on…..
8
Trigonometry f(x)=sinxf’(x)=cosx Simple steps, we learned earlier: 1. Replace x with x+h and copy problem 2. Factor and get rid of h 3. Replace h with 0 Now we are going to use these steps to prove f(x)=sinx f’(x)=cosx
9
F(x)=sinxf’(x)=cosx Lim f(x+h) – f(x)=Lim sin(x+h)-sinx h 0 hh 0h = Lim sinxcosh + cosxsinh- sinx=Lim sinx(cosh-1) + Lim cosxsinh h 0 hh 0 h h 0 h = Lim sinx (0) + Lim cosx (1)=Lim cosx h 0 h 0h 0
10
Now let’s prove that f(x)=cosxf’(x)=-sinx Lim f(x+h) – f(x)=Lim cos(x+h)-cosx h 0 hh 0 h = Lim cosxcosh - sinxsinh- cosx=Lim cosx(cosh-1) - Lim sinxsinh h 0 h h 0 h h 0 h =Lim cosx (0) – Lim sinx(1)= -sinx h 0 h 0
11
Now let’s prove that f(x)=tanxf’(x)=sec ²x *Think of f(x)=tanx as f(x)= sinx/cosx Lim = sin(x+h) – sinx H 0 cos(x+h) cosx h *now you need to find a common denominator and then flip! Lim sin(x+h) cosx – sinxcos(x+h)* _1_ H 0 _____cos (x+h) cosx_______ h __h__ 1
12
Tangent continued… Lim sin(x+h) cosx – sinxcos(x+h) H 0 h[cos(x+h) cosx] Lim (sinxcosh + cosxsinh) * cosx- sinx (coscosh – sinxsinh) H 0 hcos(x+h) * cosx Lim sinxcoshcosx + cos ²xsinh – cosxcoshsinx + sin²xsinh *cancel out H 0 h cos (x+h) cosx
13
Tangent continued… Lim sinh (sin ²x + cos²x)=Lim 1 * 1_____ h 0 h cos(x+h) cosxh 0 cos(x+h)cosx *side note: Never expand the bottom!!! Lim 1______=Lim 1___ h 0 cos(x+0)cosxh 0 cos²x *which equals sec²x!!!
14
Memorize these trig functions and their derivatives! F(x)=sinx F’(x)=cosx F(x)=cox F’(x)=-sinx F(x)=tanx F’(x)=sec ²x F(x)=cotx F’(x)=-csc ²x F(x)=secx F’(x)=secxtanx F(x)=cscx F’(x)=-cscxcotx *you can remember all the C’s have negative derivatives!
15
SHORT CUTS!!! 1. Chain Rule 2. Product Rule 3. Quotient Rule
16
Chain Rule F(x)=u ^ nF’(x)= nu ^ (n-1) The exponent goes out front and then subtract 1 from the exponent *used every time although may be embedded in product or quotient
17
Example of Chain Rule f(x)= x ³+6x *bring the 3 and multiple it by the one is front of the x. then subtract 1 from 3 (the exponent). *bring the 1 down to multiple it by the sixth. Then subtract 1 from the exponent, which in this case is zero f’(x)=3x ² +6x ºThus, f’(x)=3x²+6 *side note: derivative of any constant is 0 For example: f(x)=5f’(x)=0
18
Try Me!!! f(x)=4x ³+10x²-6x+100
19
And the answer is… f(x)= 4x ³+10x²-6x+100 f’(x)=12x ²+20x-6+0 Thus, f’(x)=12x²+20x-6
20
Product Rule Used when you are multiplying Equation: (F)(DS)+(S)(DF) F=first number or set of numbers DS=Derivative of second number S=second number or set of numbers DF=Derivative of first number For example: (x+2)(5x+2) first second
21
Example of Product Rule 1. f(x)= (2x+1)^5 (5x-3) ² 2. f’(x)=(2x+1)^5(2)(5x-3)(5) + (5x-3)²(5)(2x+1)^4 (2) 3. F’(x)= 10(2x+1)^4(5x-3)[(2x+1)+(5x-3)] 4. F’(x)= 10(2x+1)^4 (5x-3) (7x-2)
22
Try Me!!! f(x) = (4x+1) ²(1-x)³
23
And the Answer is… f(x) = (4x+1) ²(1-x)³ f’(x)=(4x+1) ²(3)(1-x)²(-1) + (1-x)³(2)(4x+1)(4) f’(x)= (4x+1)(1-x)² [-3(4x+1)+8(1-x)] f’(x)= (4x+1)(1-x)²[-12x-3+8-8x] f’(x)= (4x+1)(1-x)²[-20x+5] f’(x)= 5(4x+1)(1-x)²(-4x+1)
24
Quotient Rule Used when you are dividing. Equation: (B)(DT)-(T)(DB) B ² B= the bottom number(the denominator) DT= the derivative of the top number T= the top number (the numerator) DB= the derivative of the bottom number For example: 2+1x Top Number 5x-e Bottom Number
25
Example of Quotient Rule Y= (2-x)/(3x+1) Y’= (3x+1)(-1)-(2-x)(3) (3x+1) ² Y’=(-3x-1)=(-6=3x) (3x+1)² Y’=___-7___ (3x+1)²
26
Try Me!!! Y= 1+x ² 1-x²
27
And the Answer is… Y= 1+x ² 1-x² Y’= (1-x ²)(2x) – (1+ x ²)(-2x) (1- x ²)² Y’= 2x-2x³+2x+2x³ (1- x ²)² Y’= 4x___ (1- x ²)²
28
Natural Log When taking the derivative of natural log: 1 over the angle * the derivative of the angle For example: F(x)= ln(x ²+3x) F’(x)= 1__ * (2x+3) x ²+3x
29
Try Me Real Quick! f(x)=ln (x ³+5x²+6x)
30
And the Answer is… f(x)=ln (x ³+5x²+6x) f’(x)= 1 (3x²+10x+6) x ³+5x²+6x
31
Derivative of e f(x)=e f’(x)=e f(x)=e^2xf’(x)=2e^2x f(x)=e^10x f’(x)=10e^10x
32
When taking the derivative of an exponent *Copy function and then multiply by the derivative of exponent For example: F(x)=e ^sinx F’(x)=e^sinx (cosx)
33
ETA For only power of trig functions E= Exponent T= Trig A= Angle Copy the rest of problem! For Example: F(x)=sin^5(cosx) F’(x)= (5)sin^4(cosx)*cos(cosx)*(-sinx)
34
Let’s try one more… F(x)= tan ²x(5x²-6x+1) F’(x)=(2)tan(5x²-6x+1)*sec²(5x²-6x+1)*(10x-6) *copy rest of problem after derivative of exponent (chain rule) *copy problem after take derivative of trig
35
Let’s Try a REAl AP Multiple Choice quesiton If f(x)=sin(e^-x), then f’(x)=? a)-cos(e^-x) b)cox(e^-x)+(e^-x) c)cos(e^-x)-(e^-x) c)(e^-x) cos(e^-x) d)-(e^-x)cos(e^-x)
36
If f(x)=sin(e^-x), then f’(x)=? ANSWER:d)-(e^-x)cos(e^-x) E1. sin^0(e^-x) 1 T2.cos(e^-x) A3.(e^-x)(-1)
37
Let’s Review real quick y=(4x+1) ²(1-x)³ Y=2-x 3x+1 Y=3x^(2/3)-4x^(½)-2 Try these!
38
y=(4x+1) ²(1-x)³ Y’= (4x+1)²(3)(1-x)²(-1)+(1-x)³(2)(4x+1)(4) Y’=-3(4x+1) ²(1-x)²+8(1-x)³(4x+1) Y’=(4x+1)(1-x)²[-3(4x+1)+8(1-x)] Y’=(4x+1)(1-x)²[-12x-3+8-8x y’=(4x+1)(1-x)² 5(-4x+1)
39
Y=2-x 3x+1 Y’=(3x+1)(-1)-(2-x)(3) (3x+1) ² Y’=-3x-1-6+3x (3x+1)² y’= -7____ (3x+1) ²
40
Y=3x^(2/3)-4x^(½)-2 Y’=(2/3)(3)(x^-1/3)(1)-(4)(1/2)(x^-1/2)(1)-0 Y’=2x^-1/3-2x^-1/2 Y’=2(x^-1/3 – x^-1/2)
41
Implicit Differentiation Used when x and y are in the problem and they can’t be separated. When taking the derivative of y... You still do it in respect to x... Everything is in terms of x Dy dx always there when taking derivative of y *solve for dy/dx
42
Let’s Try one F(x)= X ²+y²=25 1. 2x+2y(dy/dx) = 0 *take derivative like normal, except whenever you take the derivative of y, you must add in dy/dx 2. *Now, solve for dy/dx 2y(dy/dx)=-2x 3. dy= -2x= -x_ dx 2y y
43
Your Turn! F(x)=(2x+1)^5+3y²=6
44
F(x)=(2x+1)^5+3y²=6 F’(x)=(5)(2x+4)^4(2)+6y(dy/dx)=0 6y(dy/dx)=-10(2x+4)^4 dy= -10(2x+1)^4 dx 6y dy= -5(2x+1)^4 dx 3y *side note: if the dy/dx were to cancel out, that means that the derivative does not exist!
45
Logarithmic Differentiation Done when there is a variable in the exponent 3 rules to remember 1. Multiplication addition 2. Division subtraction 3. Exponents multipliers
46
For example: y=2^x Lny= xln2 *RULE: when you add the ln, the exponent comes down in front as so. *now take the derivative of both sides! 1 dy = x(0)+ln2(1) y dx Dy/dx=ln2(y)*plug in your original equation for y Dy/dx=ln2(2^x)
47
Formula: *y = a^x Dy/dx = a^x lna (this would help with the first bullet on the previous slide)
48
Now your turn F(x)=x^sinx
49
F(x)=x^sinx Lny=sinxlnx 1 dy = sinx 1 (1) + lnxcosx x dx x Dy/dx= x^sinx[sinx/x + lnxcosx] ^we mult. By y!
50
Almost done... Now let’s try an FRQ 1975 AB2 This FRQ is about particle motion, which involves position, velocity and acceleration. In order to solve these kind of problems you must be able to take the derivative! For the derivative of position=velocity And the derivative of velocity=acceleration
51
1975 AB 2 Given the function f defined by f(x)=ln(x 2 -9). A. Describe the symmetry of the graph of f. B. Find the domain of f. C. Find all values of x such that f(x)=O. D. Write a formula for f -1 (x), the inverse function of f, for x >3.
52
© Laura Berglind and Avery Gibson, 2011, AP Calculus AB, Autrey THE END
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.